A prototype analysis of the portuguese concept of saudade - Felix Neto (2014)
The present research examined the way laypersons in Portugal conceptualize saudade, using Rosch's Prototype Theory. Study 1 showed that when asked to list prototypic features of saudade, each participant was able to evoke about 7 different features, which resulted in a total list of 182 separate features. Study 2 showed that when asked to rate centrality of features of saudade, each participant was able to rate features as more or less prototypical of the concept, and the range of their ratings considerably varied. It also showed that when asked to rate the affective valence of these features, each participant was able to rate features as more or less positive/negative, and the range of their responses varied from the negative to the positive scale anchors, which attested that they were fully aware of the complexity of the concept. Studies 3 and 4 showed that centrality of feature had an impact on cognition. The prototypical structure of saudade slightly interfered with free recall, more strongly interfered with recognition, and considerably impacted on story writing related with past experiences of saudade.